Spatially resolved monitoring of neutrophil elastase activity with tatiometric fluorescent reporters - Gehrig, Stefanie; Mall, Marcus A.; Schultz, Carsten (Angewandte Chemie. International edition, 2012)
Finding NEmo: In a mouse model for lung inflammation, the lipidated peptide-based ratiometric fluorescent reporter NEmo-2 indicates that neutrophil elastase (NE) activity is mainly associated with the surface of neutrophils (see scheme), whereas a soluble reporter variant showed no activity in the lung fluid, likely because of the abundance of antiproteases. Targeting the localization of NE activity has great potential for the development of improved antiinflammatory drugs.